1998
DOI: 10.1212/wnl.51.5.1263
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of epilepsy in tuberous sclerosis

Abstract: Surgical treatment of patients with TSC and intractable epilepsy is most effective when a single tuber or epileptogenic area can be identified as the source of seizures and resected. This may be possible even when other tubers or diffuse EEG abnormalities are present. In patients with unlocalizable epileptic abnormalities, palliation may be obtained by CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 8 publications
1
109
0
Order By: Relevance
“…In these first reports, the patients selected had focal electroencephalographic discharges with little ambiguity in localization. In a study of 18 patients by Guerreiro et al, 14 12 patients had focal or regional EEG abnormalities directing resection. Six of the patients, however, had multiple lesions or nonlocalizable epilepsy due to generalized EEG abnormalities.…”
Section: Epilepsy Surgery In Tscmentioning
confidence: 96%
“…In these first reports, the patients selected had focal electroencephalographic discharges with little ambiguity in localization. In a study of 18 patients by Guerreiro et al, 14 12 patients had focal or regional EEG abnormalities directing resection. Six of the patients, however, had multiple lesions or nonlocalizable epilepsy due to generalized EEG abnormalities.…”
Section: Epilepsy Surgery In Tscmentioning
confidence: 96%
“…Over the 40 years since that report, the published literature has consistently found that traditional resective epilepsy surgery can be very successful in reducing the seizure burden in carefully selected patients with TSC who harbor a single tuber and associated epileptogenic focus. 3,5,8,18,[26][27][28]34,35,37,41,52,57,75 Patients not meeting this selection criterion for surgery were offered a palliative approach, such as corpus callosotomy. 18 A review of the TSC epilepsy surgery literature indicates that patients with a well-localized single tuber and corresponding epileptogenic zone are excellent surgical candidates, but children not fitting this profile are often excluded from operative treatment because a poor outcome was anticipated.…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…Therefore, early identification of potential surgical candidates is critical for seizure control and optimal development. However, the published literature primarily contains reports on older children, 3,5,8,18,[26][27][28]34,35,37,41,52,57,75 with very few younger patients included in these series. This raises the question of whether a potential benefit is not seen because surgery is delayed beyond a potentially important developmental window.…”
Section: Neurosurg Focus / Volume 25 / September 2008mentioning
confidence: 99%
See 2 more Smart Citations